The limits of doubt : the moral and political implications of skepticism - Lom, Petr, 1968- (State University of New York Press, 2001)
"The Limits of Doubt studies the skepticism of Nietzsche, Sextus Empiricus, Hobbes, Diderot, and Montaigne in order to illustrate how different forms of skepticism can produce remarkably different implications. These include toleration; chastening of character; the prohibition of cruelty; indifference; corrosiveness of liberal principles; and freeing of the will from moral restraint. Demonstrating how skepticism is an under-determined and unstable category, accompanied by varying unquestioned intentions and beliefs, this book shows how these limits of doubt shape its various possible implications. A unique examination of skepticism from a moral and political perspective. The Limits of Doubt will interest all those concerned with the possibilities for life in an age of doubt."--Jacket